2018
DOI: 10.1007/s11250-018-1703-7
|View full text |Cite
|
Sign up to set email alerts
|

Multi-country investigation of factors influencing breeding decisions by smallholder dairy farmers in sub-Saharan Africa

Abstract: Artificial insemination (AI) and selective bull mating are considered as robust methods for dairy cattle breeding. Globally, these methods have been used to enhance productivity and realize rapid genetic gains. However, these technologies have had low adoption rates in sub-Saharan Africa (SSA). Even though available evidence suggests that this is due to various infrastructural and technical challenges. There is limited information about what drives this low uptake of AI from a farmer's perspective. Therefore, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 8 publications
1
20
0
Order By: Relevance
“…The study additionally reveals the dominance of farms characterized as small-scale, subsistence, extensive, and low productive. This is in line with previous studies that also reported that most farmers in sub-Sahara African countries are small-scale and subsistence in nature [46,84,85]. Though some studies have found small-scale farms to be more productive and efficient [86,87], others have challenged this finding, reporting that small farms are characterized by low efficiency, low productivity, and weak integration into the market [88][89][90].…”
Section: Discussionsupporting
confidence: 91%
“…The study additionally reveals the dominance of farms characterized as small-scale, subsistence, extensive, and low productive. This is in line with previous studies that also reported that most farmers in sub-Sahara African countries are small-scale and subsistence in nature [46,84,85]. Though some studies have found small-scale farms to be more productive and efficient [86,87], others have challenged this finding, reporting that small farms are characterized by low efficiency, low productivity, and weak integration into the market [88][89][90].…”
Section: Discussionsupporting
confidence: 91%
“…Most (65.0%) farmers of NKCC Sotik (state-owned processor) were in cluster 1 which was characterized by not housing cows at night, use of bull as main method of reproduction, weekly spraying of cows, and low proportion of farmers selling milk through groups. The reason for use of bull in reproduction could be as a result of farmers having large pieces of land to rear bulls (Mwanga et al 2019 ), farmers getting discouraged to use AI due to its high cost and cases of repeated inseminations that further increase costs (Mburu et al 2016 ). The finding of low use of AI services in the study area was congruent with the findings of Kenduiwa et al ( 2016 ) who studied the influence of smallholder dairy farmers’ participation in microfinance on breed improvement in dairy farming in Bomet County.…”
Section: Discussionmentioning
confidence: 99%
“…Farmers in this milkshed which is part of Central Kenya region mainly practice zero grazing due to their small pieces of land and hence limited land to graze their cows (Bebe et al 2003 ). In addition, farmers with small pieces of land may decide to intensify their farming through genetic improvement such as AI (Didanna et al 2018 ; Mwanga et al 2019 ). In contrast, to the findings of this study, a study on breeding services and factors influencing their use by smallholder dairy farmers in Central Uganda indicated that use of AI was positively influenced by the size of grazing land (Mugisha et al 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…One of the solution to answer the challenge of beef productivity is to improve the cattle reproduction with technology intervention such as Artificial Insemination (AI) (Thundathil et al, 2016). AI as a reproduction technology have been applied not only to improve productivity but also to realize rapid genetic gains (Mwanga et al, 2018). AI technology can also be accessed by smallholder farmers in relatively affordable cost expenses and may produce more healthy offspring (Rathod et al, 2017).…”
Section: Introductionmentioning
confidence: 99%